2021
DOI: 10.1371/journal.pone.0246309
|View full text |Cite
|
Sign up to set email alerts
|

Changes in contraceptive and sexual behaviours among unmarried young people in Nigeria: Evidence from nationally representative surveys

Abstract: Context Nigeria is a high-burden country in terms of young people’s health. Understanding changes in young people’s sexual and reproductive health (SRH) behaviours and the associated factors is important for framing appropriate interventions. Objective This study assessed changes in SRH behaviours of unmarried young people aged 15–24 and associated factors over a ten-year period in Nigeria. Data and method We analysed datasets from Nigeria Demographic and Health Surveys of 2008, 2013 and 2018 to assess cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 36 publications
(49 reference statements)
4
12
0
Order By: Relevance
“…About nine of every ten of the respondents were either single or unmarried. Research has shown that only a fifth of Nigerian adolescents aged 15 -19 years old are sexually active [24]Our results are in keeping with the study by Caron F., 2004 that showed that younger peers were less sexually active than their older peers. We therefore equate the probable lack of sexual experience with poor knowledge of condoms, as majority of our study population are adolescents and only a few of whom might be sexually active [24,25].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…About nine of every ten of the respondents were either single or unmarried. Research has shown that only a fifth of Nigerian adolescents aged 15 -19 years old are sexually active [24]Our results are in keeping with the study by Caron F., 2004 that showed that younger peers were less sexually active than their older peers. We therefore equate the probable lack of sexual experience with poor knowledge of condoms, as majority of our study population are adolescents and only a few of whom might be sexually active [24,25].…”
Section: Discussionsupporting
confidence: 81%
“…Research has shown that only a fifth of Nigerian adolescents aged 15 -19 years old are sexually active [24]Our results are in keeping with the study by Caron F., 2004 that showed that younger peers were less sexually active than their older peers. We therefore equate the probable lack of sexual experience with poor knowledge of condoms, as majority of our study population are adolescents and only a few of whom might be sexually active [24,25]. Also, of a possibility is that these young population groups with knowledge about family planning (FP) methods are oblivious about how-to-use contraceptive methods such as condoms.…”
Section: Discussionsupporting
confidence: 81%
“…The study revealed that 4 out of every 10 adolescents have experienced sexual intercourse and that male adolescents are more involved in sexual risk behavior than the female adolescents. While the finding could be in tandem with previous studies [ 27 ]; [ 28 ], it signals that (1) such finding is still relevant today, and (2) the understanding of the report could spur paradigm shifts in existing strategies or their modifications. Therefore, in as much as the focus of this study is not directly to evaluate international, national, or local strategic framework on Adolescent Reproductive Health Programs, the results herein are evidences of nonabsolute success of these programs, and a need for change is imperative.…”
Section: Discussionsupporting
confidence: 77%
“…Adolescent contraceptive needs which have been fulfilled is a requirement to comply Sustainable Development Goals (SDGs) 3.7 on reproductive health, which targets that by 2030, a widespread approach or use of contraceptive for all ages should be implemented to family planning (Oppong et al, 2021). Evaluating determinants in young adult contraceptive use is crucial for determining the fulfillment of preceding intervention efforts, monitoring progress on the target 3.7 of the SDGs, as well as for prioritizing destiny moves (Adedini et al, 2021). Although contraceptives might not postpone the onset of their sexual action, it is still able to anticipate the undesired pregnancy and different undesirable results (Budiharsana, 2017).…”
Section: Introductionmentioning
confidence: 99%